Characterization of catechol catabolic genes from Rhodococcus erythropolis 1CP. - Eulberg, D (1997)
The biochemical characterization of the muconate and the chloromuconate cycloisomerases of the chlorophenol-utilizing Rhodococcus erythropolis strain 1CP previously indicated that efficient chloromuconate conversion among the gram-positive bacteria might have evolved independently of that among gram-negative bacteria. Based on sequences of the N terminus and of tryptic peptides of the muconate cycloisomerase, a fragment of the corresponding gene has now been amplified and used as a probe for the cloning of catechol catabolic genes from R. erythropolis. The clone thus obtained expressed catechol 1,2-dioxygenase, muconate cycloisomerase, and muconolactone isomerase activities. Sequencing of the insert on the recombinant plasmid pRER1 revealed that the genes are transcribed in the order catA catB catC. Open reading frames downstream of catC may have a function in carbohydrate metabolism. The predicted protein sequence of the catechol 1,2-dioxygenase was identical to the one from Arthrobacter sp. strain mA3 in 59% of the positions. The chlorocatechol 1,2-dioxygenases and the chloromuconate cycloisomerases of gram-negative bacteria appear to be more closely related to the catechol 1,2-dioxygenases and muconate cycloisomerases of the gram-positive strains than to the corresponding enzymes of gram-negative bacteria.